Adjusting yearling weight ratios for prior selection - J. Vanmiddlesworth; R.R. Schalles; George A. Milliken (Kansas Agricultural Experiment Station Research Reports, 1975)
We developed a procedure to compare yearling weight ratios of a calf crop when the calves have been on different management or feeding regimes This procedure will also produce more meaningful sire and dam summaries.
Keywords: Cattlemen' s Day; 1975; Report of progress (Kansas State University. Agricultural Experiment Station); 230; Beef; Yearling weight; Weaning weight; Calf crop